Experiencias de vida de madres con hijos en condición de discapacidad visual; Revisión bibliográfica, (2022)
According to the international classification of diseases, in its report number 11 (CIE-11) and the Unique Manual for the Qualification of the Loss of Labor and Occupational Capacity decree: 1507 of 2014 in its Chapter number 11, visual disability is the loss of visual acuity. For ICD-11, visual impairment is considered from an uncorrected visual acuity of 20/60 or worse in the better eye1,2. While that for decree 1507 of 2014, visual disability is considered from a visual acuity with correction of 20/80 or worse, in the best of both eyes